Evaluating risk and vulnerability assessments: a study of the regional level in Sweden. (23rd May 2013) - Abrahamsson, Marcus; Tehler, Henrik
Risk and Vulnerability Assessments (RVA) are performed on many levels of society by many different organisations. In the present paper we discuss how one can investigate if a system for RVA used in a country or a region fulfils its intended purpose. We show how the purpose of the Swedish system can be related to the actual form of the individual RVA documents. This is followed by a content analysis of all RVAs performed by the 21 County administrative boards (regional level) in Sweden in 2008 and 2010. Several of the documents do not display the necessary properties that would allow other agencies to use them as a basis for the national overview of risks and vulnerabilities. This means that the system for RVA cannot be said to achieve one of its purposes. Implications of this are discussed and suggestions on how to address this issue are given.